Women in panchayats : a study of role conflict - Singh, U. B. 1953- (New Delhi : Serials Publications, 2011)
Study conducted in Uttar Pradesh, India.
Includes bibliographical references (p. [263]-267) and index.
Keywords: Women -- Political activity -- India -- Uttar Pradesh; Women -- Political activity -- India -- Uttar Pradesh -- Statistics; Panchayat -- India -- Uttar Pradesh; Women politicians -- India -- Uttar Pradesh -- Social conditions; Role conflict; Support (Domestic relations) -- India -- Uttar Pradesh